ESEFFEGO: imagens do pioneirismo da Educação Física em Goiânia - NASCIMENTO, Fabiana Alzira Ramos (2009)
This study aims to discuss which the body conceptions from egress students of the first graduation class from ESEFFEGO are and what role these newly graduated students had in the characterization of the Physical Education in Goiania during the 1960 s. Therefore, taking in consideration that the methodological proceedings of this research privileged the senses and meanings systems of the subjects of this investigation, we were also interested in understanding the following questions: which symbolic elements composed the body conceptions of the subjects of this research? And more: how the body conceptions of the egress students from the first graduate class articulated with the conceptions of man and society that sustained the city of Goiania during the 1960 s? And in which manner the conceptions and practices of these students consubstantiates the Physical Education as a field of knowledge in the superior education in Goiás? It is expected as result of this research the visibility of the construction of the body conceptions found in the Physical Education in ESEFFEGO and its inter-relations with the cultural and social context in the history of the superior education in the city of Goiania